Shaking-table tests of a full-scale single-story masonry veneer wood-frame structure. - Okail, Hussein O.
This paper presents the findings of shaking-table experiments conducted to examine the seismic performance of a full-scale, one-story, wood-framed structure with masonry veneer. The structure was designed and constructed in accordance with current U.S. code provisions. The veneer was attached to the wood backing with two kinds of metal anchors, corrugated ties fastened with 8d nails and rigid ties fastened with #8 screws. The tests have shown that the use of nails to fasten veneer anchors to the wood studs is highly unreliable due to the high variation of the nail extraction capacity, which can be influenced by the moisture content of the wood. Other than this, both the wood frame and the masonry veneer performed well under severe ground motions far exceeding a design level earthquake for Seismic Design Category D. Good performance was observed for the rigid veneer ties, which were attached to the wood studs with screws. The results have shown that the veneer walls parallel to the direction of shaking helped to restrain the motion of the wood structure and therefore should not be simply treated as added mass. The detailing of wood roof diaphragms requires special attention in consideration of the out-of-plane inertia force of the veneer that can be transmitted through the top plate of the wood-stud wall to the rim joist.
Keywords: Seismic performance; Shaking-table tests; Masonry; Veneer; Brick; Wood frames; Corrugated ties; Rigid ties; Joint reinforcement